2019
DOI: 10.1155/2019/5743952
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Variation of a Kind of Protein Staining and Food Dye as a New Corrosion Inhibitor on Mild Steel in Acidic Medium

Abstract: In this study, the relevance of a food dye, namely, Fast Green-FCF (FG-FCF), was surveyed as a new inhibitor for mild steel in HCl solution. This effect was specified by electrochemical impedance spectroscopy (EIS), one of the most widely used measurement techniques. As a result of the increment of the inhibitor concentration, it was seen that the values ​​of polarization resistance increased and covered the metal surface of FG-FCF like a blanket. Tests endorse that the FG-FCF is chemically adsorbed on mild st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The study of corrosion process and its inhibition by organic compounds, such as dyes, is a very active field of research in acidic or basic environments [7][8][9][10][11][12][13]. Dyes have long been applied in the coloring, printing, paper, leather, textile, plastics, cosmetic, medical, pharmaceutical, and agri-food industries, and in recent times as corrosion inhibitors of metals and alloys in aggressive environments [14,15].…”
mentioning
confidence: 99%
“…The study of corrosion process and its inhibition by organic compounds, such as dyes, is a very active field of research in acidic or basic environments [7][8][9][10][11][12][13]. Dyes have long been applied in the coloring, printing, paper, leather, textile, plastics, cosmetic, medical, pharmaceutical, and agri-food industries, and in recent times as corrosion inhibitors of metals and alloys in aggressive environments [14,15].…”
mentioning
confidence: 99%
“…Impedance spectroscopy is one of the fastest and easiest methods that are often preferred in researching the protective properties of all these molecules on metals in aggressive solutions, whether the inhibitor used is organic molecules or inhibitors of plant origin. [22][23][24] For this reason, electrochemical behaviour of mild steel was evaluated by measuring with EIS at the end of one, 24 and 120 h immersion times in 1.0 M HCl solutions containing four different concentrations of Lavandula (0.100%, 0.050%, 0.300% and 0.500% (w/v)) and not containing inhibitor. The equivalent circuits of the corrosion process were constituted from these results by utilizing Zview2 software.…”
Section: Evaluation Of Eis Findingsmentioning
confidence: 99%
“…Studies on corrosion inhibition performance of dyes have shown that organic dyes are effective in retarding the corrosion in acid or base environments. 3,4 Different types of dyes are commercially available. They are produced annually to be applied in various domains including paper industries, printing, plastics, cosmetics, leather, textile industry, pharmaceuticals, agrofood industries and medical industry.…”
Section: Introductionmentioning
confidence: 99%